Biomechanics of the continuity and speed change during one revolution of the Fouette turn - Imura, A.; Iino, Y.; Kojima, T. (Human Movement Science, 2009)
The purpose of this study was to investigate the biomechanics of the continuity and speed change of the Fouette turn. This turn is one of the turns performed on one leg in classical ballet and is unique in terms of its continuity and change in rotational speed of the torso during one revolution of the turn. We filmed the turn as performed by seven experienced female ballet dancers in a clockwise direction on a force plate using three high speed cine cameras. In a 3D motion analysis of the turn, we found that the dancers mainly controlled the rotational speed by swinging the free or gesture leg laterally through torque exertion at the hip joint of the leg in clockwise and then counterclockwise directions, and that they supplied an angular impulse mainly to the gesture leg during the swing when flexing the supporting leg and keeping their foot flat on the plate. This supply of momentum enabled them to continue the turn compensating for the loss of the momentum of the body brought about in a rapid rotation phase when they were standing on tiptoe touching the foot of the gesture leg on the knee of the supporting leg.